Impaired NLRP3 inflammasome signaling diverts pyroptotic to apoptotic caspase activation in macrophages - Gan, Ying-qing; Cai, Yuan-wen; Liang, Xiu-wen; Wang, Ling-Zhi; Shi, Fu-li; Sun, Nuo; Li, Ya-ping; Xu, Rong; Hu, Bo; Zha, Qing-bing; He, Xian-hui; Wong, Tak-sui; et al. (Frontiers in Immunology, 2025)
NLRP3 (NLR family pyrin domain-containing 3) inflammasome is a first line of defense of innate immunity, mediating caspase-1-dependent pyroptosis and cytokine release upon danger signaling. Intervention of NLRP3 innate surveillance may cause defects in this signaling pathway, while the host has evolved alternative ways to combat such intervention. Yet it remains incompletely understood whether NLRP3 sensing of danger signaling can divert pyroptosis to other forms of cell death in circumstances of impaired NLRP3 signaling. In this study, we adopted two macrophage models (delayed delivery of triggering signaling and caspase-1 deficiency) to mimic defects in NLRP3 signaling to address this issue. We found that the NLRP3/ASC platform preferentially recruited caspase-1 rather than caspase-8 in lipopolysaccharide (LPS)-primed macrophages timely triggered with nigericin. However, when the triggering signal (nigericin) was delayed, the recruitment diverted to caspase-8, leading to apoptotic caspase activation. Furthermore, in caspase-1-deficient macrophages, nigericin triggering diverted NLRP3-ASC-caspase-1-driven pyroptosis to caspase-8/-9/-3 activation and GSDME-mediated secondary necrosis. Unexpectedly, VX-765 (a caspase-1 inhibitor) exhibited a pan-caspase inhibitor-like effect, suppressing caspase-8/-9/-3 activation and GSDME cleavage in a dose-dependent manner. Mitochondrial damage was observed in both WT and caspase-1-deficient cells upon nigericin stimulation, suggesting mitochondrial injury being an upstream event in this process. Collectively, our data indicate that NLRP3 inflammasome is poised to divert pyroptotic to apoptotic caspase activation for combating danger signaling when conventional pathway is impaired, highlighting a complex interaction between various forms of cell death pathways.